2011
DOI: 10.1021/bi200058a
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Barley NADPH-Dependent Thioredoxin Reductase C Is Independent of the Oligomeric State of the Protein: Tetrameric Structure Determined by Cryo-Electron Microscopy

Abstract: Thioredoxin and thioredoxin reductase can regulate cell metabolism through redox regulation of disulfide bridges or through removal of H(2)O(2). These two enzymatic functions are combined in NADPH-dependent thioredoxin reductase C (NTRC), which contains an N-terminal thioredoxin reductase domain fused with a C-terminal thioredoxin domain. Rice NTRC exists in different oligomeric states, depending on the absence or presence of its NADPH cofactor. It has been suggested that the different oligomeric states may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Cotransformation of tobacco cells with NTRC-G1 or NTRC-G3 (NTRC fused to either the N-or C-terminal part of the Venus protein) was used as a positive BiFC control. This dimerization of NTRC confirmed previous findings Wulff et al, 2011). Coinfiltration of A. tumefaciens with vectors for the expression of CHLM-G3 and GluTR-G1 (and reverse combinations) did not result in yellow fluorescence and was used as a negative control (Fig.…”
Section: Ntrc Interacts With Glutr1 and Chlmsupporting
confidence: 90%
See 1 more Smart Citation
“…Cotransformation of tobacco cells with NTRC-G1 or NTRC-G3 (NTRC fused to either the N-or C-terminal part of the Venus protein) was used as a positive BiFC control. This dimerization of NTRC confirmed previous findings Wulff et al, 2011). Coinfiltration of A. tumefaciens with vectors for the expression of CHLM-G3 and GluTR-G1 (and reverse combinations) did not result in yellow fluorescence and was used as a negative control (Fig.…”
Section: Ntrc Interacts With Glutr1 and Chlmsupporting
confidence: 90%
“…NTRC and GluTR also form homodimers. The BIFC-mediated dimerization of NTRC corroborates the previous report on the dimeric structure of the NTRC (Wulff et al, 2011). Second, the addition of NTRC stimulates the activity of purified MgP methyltransferase and substitutes DTT in the in vitro enzyme assay (Fig.…”
Section: Ntrc Is a Posttranslational Regulator Of Chl Biosynthesissupporting
confidence: 89%
“…The NTRd and the TRXd sequence alignments were then combined into one alignment, which was used for modeling ( Figure 2 ). The linker region connecting the NTRd to the TRXd was determined based on sequence alignment with barley NTRC, which has an approximately 35 amino acids long linker between residues 341 and 374 (Wulff et al, 2011). Arabidopsis NTRC shares 81 % identity to barley NTRC, indicating a similar linker region.…”
Section: Methodsmentioning
confidence: 99%
“…In-vitro assays with purified NTRC and its target proteins support the model, demonstrating that the NTRd of NTRC primarily reduces its own TRXd, whereas it has a poor capability of reacting with other chloroplast TRXs (Pérez-Ruiz and Cejudo, 2009; Bohrer et al, 2012; Lee et al, 2012). However, recombinant NTRC protein forms oligomeric aggregates in vitro (Wulff et al, 2011) that may inhibit the interactions of NTRC with other chloroplast TRXs. To study the action of the NTRC domains in vivo , we have complemented the ntrc knockout line with a wild type NTRC gene and with full-length genes, in which the redox-active Cys motif in the NTRd (C217S/C220S) or in the TRXd (C454S/C457S) was inactivated.…”
Section: Introductionmentioning
confidence: 99%
“…In the letter case, the mutant phenotypes are restored by supplementing growth medium with tryptophan and phenylalanine. Interestingly, it has been reported that the protein structures of NTRC have various oligomeric conformations in other species like rice, barrel medic, and barley (Alkhalfioui et al, 2007; Perez-Ruiz and Cejudo, 2009; Wulff et al, 2011). That is, NTRC assembles into homopolymeric structures of varying complexity with functions as a disulfide reductase, a foldase chaperone, and as a holdase chaperone.…”
Section: Functional Switching Of Redox Proteins Accompanying With Thementioning
confidence: 99%